Bidirectional ventricular tachycardia of unusual etiology - Praloy Chakraborty (Indian Pacing and Electrophysiology Journal, 2015)
Bidirectional ventricular tachycardia (BDVT) is a rare form of ventricular arrhythmia, characterized by changing QRS axis of 180 degrees. Digitalis toxicity is considered as commonest cause of BDVT; other causes include aconite toxicity, myocarditis, myocardial infarction, metastatic cardiac tumour and cardiac channelopathies. We describe a case of BDVT in a patient with Anderson-Tawil syndrome.